-Son Değişiklikler Kapsamında- Kamu Hizmeti İmtiyaz Sözleşmeleri Uyuşmazlıklarında “Tahkim” / -In the Context of the Recent Amendments- "Arbitration" In Public Service Concession Agreement Disputes - Dolunay, Ayhan (Journal of History Culture and Art Research, 2018)
ABSTRACT Public law concession agreements, contracts between administrative and private law real or legal entities. Contracts aimed at ensuring the provision of services without undergoing high financial "burdens". In the case of disputes concerning public service concession agreements, preference is given to the settlement disputes with arbitral jurisdiction rather than settlement of court disputes, usually by private contracting parties. In our work, firstly we will give information about the concept of public service concession agreement and arbitration, then, in the Turkish administrative law, the "obstruction of arbitration", which will rule until 1999, and the elimination of the ban will be discussed. Later, the elements and procedure of the arbitration will be examined in detail in the context of "recent changes", followed by the determination of the substantive rules of law to be applied to the merits of the dispute in the arbitration proceedings, and finally, to be given information about the decisions to be made on the basis of the arbitration proceedings. ÖZ Kamu hukuku imtiyaz sözleşmeleri, idare ve özel hukuk gerçek ya da tüzel kişileri arasında akdedilen ve idarenin, teknoloji, iş gücü vb. konularda, yüksek mali “yük”ler altına girmeksizin, hizmet sağlanmasını amaçlayan sözleşmelerdir. Kamu hizmeti imtiyaz sözleşmeleri ile ilgili söz konusu olabilecek uyuşmazlıklarda ise, sözleşmeye taraf özel hukuk kişilerince, genellikle, mahkemelerce uyuşmazlığın çözümü yerine, tahkim yargılaması ile uyuşmazlığın çözümü tercih edilmektedir. Çalışmamızda, öncelikle, kamu hizmeti imtiyaz sözleşmesi ve tahkim kavramları hakkında bilgi verilecek, ardından, Türk idare hukukunda, 1999 yılına kadar egemen olan “tahkim yasağı” ve yasağın bertaraf edilmesi hususları ele alınacaktır. Sonrasında ise, tahkim yargılamasının unsurları ve usulü detaylı olarak, “son değişiklikler kapsamında” incelenecek, ardından, tahkim yargılamasında ihtilafın esasına uygulanacak maddi hukuk kurallarının tespiti ve son olarak da, tahkim yargılaması neticesinde hükmolunacak kararların icrası hakkında bilgi verilecektir.